2021
DOI: 10.3389/fpsyg.2021.779277
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics and Sociodemographic Adaptation of the Corrigan Agitated Behavior Scale in Patients With Severe Mental Disorders

Abstract: Background: Severe mental disorder (SMD) is understood in a first approximation as a disorder of thought, emotion, or behavior of long duration, which entails a variable degree of disability and social dysfunction. One of the most widely used assessment scales for agitated behavior, in its English version, is the Corrigan Agitated Behavior Scale (ABS); several studies have demonstrated solid psychometric properties of the English version, with adequate internal consistency.Objective: The objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Various studies have shown the sound psychometric properties of the English version, with a Cronbach’s alpha of between 0.801 and 0.921 [ 13 , 33 , 34 , 41 ]. The recent study of the Spanish version of the scale shows complete consistency (0.9 Cronbach’s alpha), as well as the consistency of each of the three domains of which it is made up [ 35 ] (0.8 disinhibition, 0.8 aggressiveness and 0.7 lability), with similar values to those found in the original version [ 33 ].…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Various studies have shown the sound psychometric properties of the English version, with a Cronbach’s alpha of between 0.801 and 0.921 [ 13 , 33 , 34 , 41 ]. The recent study of the Spanish version of the scale shows complete consistency (0.9 Cronbach’s alpha), as well as the consistency of each of the three domains of which it is made up [ 35 ] (0.8 disinhibition, 0.8 aggressiveness and 0.7 lability), with similar values to those found in the original version [ 33 ].…”
Section: Methodsmentioning
confidence: 82%
“…One of the most used scales for assessing agitated behaviour is Corrigan’s Agitated Behaviour Scale (ABS), which provides quantitative and qualitative information, allowing to know the severity of agitation and its properties in terms of lability, disinhibition and aggressiveness [ 33 , 34 ]. It has been mostly used in the assessment of psychomotor agitation in mental health settings [ 13 , 34 , 35 , 36 , 37 ]. This evaluation can be completed with the assessment of associated nursing diagnoses, according to the North American Nursing Diagnosis Association (NANDA).…”
Section: Introductionmentioning
confidence: 99%
“…All the tools used to develop the "Chem-Sex Inventory" (CSI) questionnaire have been validated in the Spanish environment. The first block related to anxiety consisting of 7 items (from 1-7) (GAD 7) [26]; the second block associated with depression (PHQ-9) [27] consisting of 9 items (from 8-16 items), the third block related to the risk of psycho (PQ-B) [28], Scale of Corrigan [29], and CAPE-15 scale [30], consisting of 21 items (from 17-37), 14 items (from 88-99), and 15 items (from 100-114), respectively, the fourth block related to impulsivity (BIS-11) [31] consisting of 30 items (from 38-67), the fifth block associated with body perception (PHQ-15) [32] composed of 15 items (from 68-82), and finally the sixth block related to suicide risk and consisting of 5 items (from 83-87) (Paykel Scale) [33]. The researchers initially eliminated two items associated with hospital admission from the Corrigan Scale.…”
Section: Item Bank Constructionmentioning
confidence: 99%
“…One of the most widely used scales for the assessment of psychomotor agitation is the Corrigan Agitated Behaviour Scale [ 11 ], which provides both quantitative and qualitative data, determining the level of agitation and its characteristics in terms of the dimensions of lability, disinhibition, and aggressiveness associated with the agitation episode. This scale has been widely used in the assessment of psychomotor agitation in patients with severe mental disorders [ 12 14 ] and can be completed with the assessment of associated nursing diagnoses (ND), such as violence directed at professionals and the environment (00138) and violence to other patients and self-directed violence (00140), according to the North American Nursing Diagnosis Association - NANDA [ 15 ]. The ND is defined as a clinical judgement about the responses of the individual, family, or community to actual or potential health problems or life processes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%